Fe-doped reconstruction of pyrite into defective Fe1-xS polymorphs for selective Cu-As separation from waste acid - Xingfei Zhang; Hongzhen Lei; Xianzhong Bu; Haisheng Han; Wei Sun; Chenglong Lu; Zihao Sun; Xuewen Song; Sen Wang; Jiwei Xue (Minerals Engineering, 2026)

Dissolved organic matter molecular composition links water chemistry, microbial functional potential, and nitrous oxide variability in a temperate estuary - Chenglong Han; Qianqian Li; Xinyi Li; Zixu Wang; Xue Yu; Xueqiang Lu (Water Research, 2026)

Anisotropy of magnetic susceptibility in the Late Cretaceous Shanyang Basin, Central China: Implications for hydrological variability and dinosaur habitat stability - Yuqi Han; Fei Han; Chen Wen; Huafeng Qin; Huapei Wang; Qiang Wang; Xinying Zhou; Chenglong Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Internal plasticization and in-situ siloxane crosslinking synergistic strategy for enhancing wet-state strength and flexibility of regenerated cellulose films - Han Gao; Ao Zhai; Ajoy Kanti Mondal; Jinwen Hu; Yehan Tao; Yanna Lv; Jian Du; Chenglong Fu; Haisong Wang (Carbohydrate Polymers, 2026)

Greenness and climate resilience: Buffering extreme weather-related depression in older adults in China - Jiaxin Han; Chenglong Wang (Sustainable Cities and Society, 2026)

Nanodomain engineering via lattice softening enables high-efficiency electromagnetic absorption in hexagonal YMnO3 ferroelectrics - Mei Su; Shuhan Dai; Chao Guo; Chenglong He; Shengxi Feng; Yanhong Hu; Ningning Sun; Pei Han; Yong Li (Chemical Engineering Journal, 2026)

Transparent cellulose films: Preparation, functionalization, and applications in food packaging - Han Gao; Ao Zhai; Linmin Xia; Jinwen Hu; Yehan Tao; Yanna Lv; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Carbohydrate Polymers, 2026)

Three-dimensional dust distribution and transport over the northern hemisphere dust belt: Insights from lidar observations - Ruiqi Tan; Tianhe Wang; Ying Han; Jingtao Li; Jingyi Tang; Sichen Wang; Ali Mamtimin; Fan Yang; Chenglong Zhou; Bakhriddin E. Nishonov; Mansur O. Amonov; Sabur F. Abdullaev (Atmospheric Research, 2026)

Revealing dissolved organic nitrogen transformation during the oxic process in 50 full-scale sewage treatment plants: Molecular and microbial mechanism - Jiaqian You; Kewei Liao; Chenglong Han; Hongqiang Ren; Haidong Hu (Journal of Environmental Management, 2026)

Quantifying the impact of nanoplastics and natural particles on copper accumulation and distribution in zebrafish: Coupling in vivo tests with toxicokinetic modeling - Xiaorong Luo; Xue Yu; Chenglong Han; Ning Gao; Xunqiang Mo; Jianfeng Feng; Xueqiang Lu (Environmental Pollution, 2026)

Phase-regulated colloidal FeS for controlled sulfidation and precise copper–arsenic separation under strongly acidic conditions - Xingfei Zhang; Wei Sun; Haisheng Han; Xianzhong Bu; Sen Wang; Xuewen Song; Chenglong Lu; Jiwei Xue; He Wan; Chonghui Zhang (Process Safety and Environmental Protection, 2025)

Rapidly evaluating electrochemical performance of transition metal disulfides for lithium ion batteries using machine learning classifier - Kun Han; Junfeng Li; Zhushun Zhang; Chenglong Wang; Jiabao Li; Yue Zhu; Zhijing Zhu; Xinjuan Liu; Guang Yang; Likun Pan (Chemical Engineering Journal, 2025)

Riverine fluxes of dissolved inorganic nitrogen may be underestimated in gated estuaries: influence of suspended sediments - Chenglong Han; Lichun Pu; Shiyu Wang; Rolf D. Vogt; Xueqiang Lu (Journal of Oceanology and Limnology, 2025)

CTAB-Assisted, controlled preparation of a CeZrOx/CuSAPO-34 catalyst and its performance for the synergistic removal of NOx and toluene from flue gas - Qian Zhou; Xuehui Jia; Rong Liu; Fangfei Liu; Han Zhang; Dan Hou; Lu Wang; Yunkuo Luo; Bichun Huang; Hong Huang; Xia Gong; Chenglong Yu (Journal of Environmental Chemical Engineering, 2025)

Agricultural waste–derived Bio-C/MoS2 anode enhances microbe–electrode interactions to reduce DOM toxicity in actual industrial wastewater - Jiahao Liao; Chenglong Han; Kewei Liao; Hongqiang Ren; Haidong Hu (Journal of Hazardous Materials, 2025)

Enriched Krylov subspace method for resolving interferometric parameter block adjustment model in elevation calibration of spaceborne InSAR digital surface model - Liqun Liu; Haiqiang Fu; Chenglong Cao; Yifan Zhang; Kun Han; Xun Du; Pengfei Li; Jie Li; Zhiwei Li (Journal of Geodesy, 2025)

Deciphering drought adaptation in Eucommia ulmoides: From the rhizosphere microbiota to root metabolites - Xueqian Zhang; Shuangshuang Hou; Xinyu Ma; Chenglong Li; Qingsong Ran; Yanfeng Han; Chunbo Dong (Applied Soil Ecology, 2025)

Neighboring clusters as additional adsorption sites to regulate the selectivity of single-atom catalysis - Xuan Zheng; Shifei Ding; Yi Lu; Jian Cai; Jiace Hao; Zechao Zhuang; Chenglong Wang; Mingliang Du; Han Zhu (Chemical Engineering Journal, 2025)

Grazing intensity modifies alpine grassland fine root traits on the Qinghai-Tibetan Plateau - Mingxue Xiang; Ruikang Luo; Junxi Wu; Ben Niu; Ying Pan; Xianzhou Zhang; Lha Duo; Tao Ma; Chenglong Han (Plant Ecology, 2025)

Eucommia ulmoides adapts to drought stress by recruiting rhizosphere microbes to upregulate specific functions - Chunbo Dong; Yongqiang Liu; Anrui Hu; Chenglong Li; Xueqian Zhang; Qiuyu Shao; Qingsong Ran; Xu Li; Yanfeng Han (Biology and Fertility of Soils, 2025)

A lightweight prediction model for global ionospheric total electron content based on attention-BiLSTM - Chao Han; Yaping Guo; Ming Ou; Dandan Wang; Chenglong Song; Ruimin Jin; Weimin Zhen; Peirui Bai; Xiaorui Chong; Xiaoni Wang (Advances in Space Research, 2025)

Far-field response to the closure of the Meso-Tethys Ocean: New geochronological evidence from the Chem Co graben in the westernmost part of Central Tibet - Yong Zheng; Jiawei Pan; Haibing Li; Zuolin Tian; Dongliang Liu; Mingkun Bai; Shuai Han; Chenglong Ge; Haijian Lu; Ning Zhong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Synergistic functionality of metal–organic framework-cellulose composites structures for advanced high-performance energy materials - Chenglong Fu; Xianxin Han; Yu Zhang; Jinwen Hu; Jian Du; Haisong Wang (Chemical Engineering Journal, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.

Dissolved organic nitrogen depresses the expected outcome of wastewater treatment upgrading on effluent eutrophication potential mitigation: Molecular mechanistic insight - Kewei Liao; Jiaqian You; Chenglong Han; Huazai Cheng; Hongqiang Ren; Haidong Hu (Water Research, 2024)

Unveiling electron transfer and radical transformation pathways in coupled electrocatalysis and persulfate oxidation reactions for complex pollutant removal - Shuai Li; Xueding Jiang; Weicheng Xu; Meng Li; Zhang Liu; Wei Han; Chenglong Yu; Jiesen Li; Hailong Wang; King Lun Yeung (Water Research, 2024)

miRNAs are involved in regulating the formation of recovery tissues in virus infected Nicotiana tabacum - Jingya Zhou; Hongyan Han; Sucen Liu; Chenglong Ji; Bolei Jiao; Yiting Yang; Dehui Xi (Molecular Genetics and Genomics, 2024)

Climate change contributed to the disappearance of the latest Cretaceous dinosaurs in the Shanyang Basin, Central China - Fei Han; Yuqi Han; Xinying Zhou; Huapei Wang; Huafeng Qin; Qiang Wang; Chenglong Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Hydrogel microspheres for stem cell recruitment and induction of directed differentiation in osteoarthritis therapy - Han Yu; Huanhuan Luo; Jianping Chen; Xiaodong Hu; Yujiong Chen; Jiaqi Zhong; Botao Liu; Yanfang Liu; Gang Chen; Chenglong Huang; Zhaoxiang Peng (Chemical Engineering Journal, 2024)

Comparison of floating and traditional artificial reef areas using an ecosystem-based approach in the Dashentang area of Bohai Bay, China - Chenglong Han; Xiaoke Pang; Wanni Liu; Wenjing Fu; Biao Guo; Toshihisa Kinoshita; Debin Zheng; Osamu Yamashita; Jianfeng Feng; Xueqiang Lu (Fisheries Research, 2024)

Intermittent polarization: A promising strategy for microbial electricity driven reduction of DOM toxicity in actual industrial wastewater - Chenglong Han; Jiaqian You; Aixia Zhao; Kewei Liao; Hongqiang Ren; Haidong Hu (Water Research, 2024)

Effects of dietary astaxanthin on growth performance, immunity, and tissue composition in largemouth bass, Micropterus salmoides - Jiankun Zhang; Yeshun Yang; Hanying Xu; Xinyu Li; Fen Dong; Qiang Chen; Tao Han; Jiteng Wang; Chenglong Wu (Frontiers in Marine Science, 2024)
This study examined the effects of feeding largemouth bass ( Micropterus salmoides ) with diets containing different doses of astaxanthin (0, 50, 100, 150, and 200 mg/kg) for 8 weeks. The results showed that the values of weight gain significantly increased from 620.32 ± 50.38% to 826.14 ± 33.49% as dietary astaxanthin levels increased from 0 mg/kg to 100 mg/kg. When the astaxanthin level exceeded 150mg/kg, the weight gain rate showed a downward trend, but there was no significant difference among of the 100, 150 and 200 mg/kg groups. The feed conversion ratio (FCR) and protein efficiency ratio (PER) were also improved by adding astaxanthin to diets ( P < 0.05). Meanwhile, adding astaxanthin to the feed increased the length and thickness of intestinal villus and muscle layer thickness ( P < 0.05). The astaxanthin supplementation increased the expression of the NF-E2-related factor ( Nrf2 ) gene and reduced malondialdehyde (MDA) content and the expression of apoptosis genes Caspase-9 and Caspase-3 ( P < 0.05), indicating that it has a good antioxidant ability. Furthermore, adding astaxanthin increased the content of non-specific immune markers and decreased the expression levels of the inflammatory factors interleukin-15 ( IL-15 ) and tumor necrosis factor-α ( TNF-α ). Moreover, fish fed diets with astaxanthin exhibited lower blood cortisol levels ( P < 0.05). The proportions of C20:4n6 (ARA) and C20:5n3 (EPA) in the liver decreased with increasing dietary astaxanthin levels. Based on WGR and SGR values, the optimal addition level of astaxanthin in largemouth bass feed is 134.8 mg/kg ~ 135.75 mg/kg. In summary, the appropriate dietary astaxanthin enhanced the antioxidant capacity and immune response of largemouth bass and had a positive effect on its intestinal health.

Artificial intelligence optimization and controllable slow-release iron sulfide realizes efficient separation of copper and arsenic in strongly acidic wastewater - Xingfei Zhang; Chenglong Lu; Jia Tian; Liqiang Zeng; Yufeng Wang; Wei Sun; Haisheng Han; Jianhua Kang (Journal of Environmental Sciences, 2024)

Effects of tillage regime on soil aggregate-associated carbon, enzyme activity, and microbial community structure in a semiarid agroecosystem - Chenglong Han; Weidi Zhou; Yanjie Gu; Junqiang Wang; Yanfang Zhou; Yunyin Xue; Zhiguo Shi; Kadambot H. M. Siddique (Plant and Soil, 2024)

Structural characterization of steranes and hopanes in petroleum by ion mobility mass spectrometry - Chenglong Dong; Jing Xie; Zhaoyang Fan; Yinghao Wang; Jikun Liu; Haodong Wang; Guangyou Zhu; Yehua Han (Fuel, 2024)

Research on coal crushing behavior under supercritical CO2 transient high-pressure fracturing - Yunzhuo Li; Huaijun Ji; Shaobin Hu; Xu Liu; Chenglong Zhang; Chu Han (Gas Science and Engineering, 2024)

Chattonella marina blooms in a trophic gradient system: Interaction with environmental drivers - Yongqi Tang; Mengyao Xu; Mengke Zhang; Chenglong Han; Jun Wei; Bo Zhang; Xueqiang Lu (Marine Pollution Bulletin, 2024)

Even carbon number predominance observed in C50-C110 n-alkanes and monocyclic alkanes in the highly mature source rock - Chenglong Dong; Jia Wu; Jikun Liu; Weilai Zhang; Sara Grimay; Peng Fang; Xiaowan Tao; Guangyou Zhu; Yehua Han (Fuel, 2024)

Physicochemical and biological changes on naturally aged microplastic surfaces in real environments over 10 months - Xue Yu; Bing Wang; Chenglong Han; Ling Liu; Xiaoxin Han; Boyang Zheng; Bo Zhang; Jiawei Sun; Zhiyin Zhang; Weiqi Ma; Lifang Zhai; Xueqiang Lu (Environmental Pollution, 2023)

Nanoplastics enhance the intestinal damage and genotoxicity of sulfamethoxazole to medaka juveniles (Oryzias melastigma) in coastal environment - Xue Li; Jiwei Luo; Chenglong Han; Xueqiang Lu (Science of The Total Environment, 2023)

The influence of annealing temperature on NH3-SCR performance of Ce Zr1-/UiO-66 bimetal MOFs - Zhitao Han; Yuqing Hu; Tingjun Liu; Chenglong Li; Song Zhou; Xinxiang Pan (Journal of Environmental Chemical Engineering, 2023)

In-depth profiling of carbohydrate isomers in biological tissues by chemical derivatization-assisted mass spectrometry imaging - Lei Wang; Yuhao Han; Yaqi Zhang; Haoyuan Geng; Zihan Zhu; Panpan Chen; Xiaoqing Cui; Xiao Wang; Chenglong Sun (Analytica Chimica Acta, 2023)

Climatic effect from oyster reef restoration in Spartina alterniflora invaded intertidal mudflat: From the perspective of CH4 and N2O production - Wenjing Fu; Xiaoke Pang; Yifan Zhao; Chenglong Han; Yufei Liu; Xue Yu; Jianfeng Feng; Jing Fang; Bo Zhang; Xueqiang Lu (Estuarine, Coastal and Shelf Science, 2023)

Specialist species of fungi and bacteria are more important than the intermediate and generalist species in near-urban agricultural soils - Yulian Ren; Wei Ge; Chunbo Dong; Haiyan Wang; Shui Zhao; Chenglong Li; Jinhui Xu; Zongqi Liang; Yanfeng Han (Applied Soil Ecology, 2023)

Assessing the Attractive Effects of Floating Artificial Reefs and Combination Reefs on Six Local Marine Species - Chenglong Han; Kefeng Liu; Toshihisa Kinoshita; Biao Guo; Yifan Zhao; Yuhang Ye; Yufei Liu; Osamu Yamashita; Debin Zheng; Wenhui Wang; Xueqiang Lu (Fishes, 2023)
Artificial reefs (ARs) have been advocated for and implemented as management tools for recreational fisheries, species conservation, and habitat replacement; however, the research that includes attracting marine species of floating ARs remains in its early stages. Here, two types of floating ARs were designed to evaluate the attractive effects using the occurrence rate and attracting index for six commercially important species (Lateolabrax maculatus, Liza haematocheila, Sebastes schlegelii, Acanthopagrus schlegelii, Litopenaeus vannamei, and Amphioctopus fangsiao) in the Bohai Bay of China; their combined ARs were meanwhile compared with two variants of artificial seagrass beds (SA and SB) and the traditional double-frame artificial reef (TD). All of the designed ARs were effective in attracting experimental species. The ARs with higher shelter areas (SB and TD) showed a better attracting effect. The efficiency of the ARs in attracting different species depended on their life histories. The bottom-mounted ARs were more efficient in attracting demersal species, while the floating ARs attracted epipelagic fish. In addition, the combined reefs had a better attractive effect than single ARs did. Overall, floating ARs and their combined ARs show the potential to deploy especially for attracting epipelagic fishes, although further study is needed.

Molecular cloning, characterization, and expression patterns of the hatching enzyme genes during embryonic development of pikeperch (Sander lucioperca) - Chenglong Pan; Lingling Li; Hao Zhu; Wenjia Mao; Tao Han; Xuqian Zhao; Caijuan Li; Qufei Ling (Aquaculture International, 2023)

Reassessing the age of the Early Pleistocene Longgupo fauna, southern China: An updated magnetostratigraphic perspective - LU SUN; CHENGLONG DENG; CAICAI LIU; JUNYI GE; SHIXIA YANG; SHUAI ZHANG; FEI HAN; JEAN‐JACQUES BAHAIN; MICHEL RASSE; ÉRIC BOËDA; YAMEI HOU; GUANGBIAO WEI; et al. (Journal of Quaternary Science, 2023)
As the northernmost locality yielding one of the most representative Early Pleistocene Gigantopithecus – Sinomastodon faunas in southern China, the Longgupo site has preserved valuable geological archives that have significantly improved our understanding of Pleistocene biostratigraphy and biogeography. A convincing chronological framework of this locality is therefore important to elaborate on the evolution of Quaternary faunas as well as paleoenvironment. To reconcile the existing geochronological results with new advances in geochronology and biochronology, we present here a revised magnetostratigraphic age model based on detailed rock magnetic and paleomagnetic data and strengthened by biochronology as well as recently published electron spin resonance and uranium series (ESR/U‐series) age data. Two geomagnetic polarities were identified from the Longgupo sequence: the upper one is thin and normal, corresponding to the Olduvai normal subchron; and the lower one is distinctly thick and reversed, corresponding to the pre‐Olduvai Matuyama Chron. The age of the Longgupo fauna constrained by this refined magnetochronological framework is therefore estimated to be about 2.5–2.0 Ma, consistent with the newly published ESR/U‐series age of 2.5–2.2 Ma.

Double-bond equivalence linear equations for structural interpretation of fossil hydrocarbons - Chenglong Dong; Wenya Hu; Yinghao Wang; Yanfen Zhang; Guangyou Zhu; Yehua Han (Fuel, 2023)

Defective Autophagy and Mitophagy in Alzheimer’s Disease: Mechanisms and Translational Implications - Jie Chen; Hai-Jun He; Qianqian Ye; Feifei Feng; Wen-Wen Wang; Yingying Gu; Ruiyu Han; Chenglong Xie (Molecular Neurobiology, 2021)

Changes in distribution and morphology of Tamarix ramosissima nebkhas in an oasis-desert ecotone - Chaofan Li; Fan Yang; Xinqian Zheng; Zhangyong Han; Honglin Pan; Chenglong Zhou; Chunrong Ji (Geosciences Journal, 2021)

Basidiomycete‐specific PsCaMKL1 encoding a CaMK‐like protein kinase is required for full virulence of Puccinia striiformis f. sp. tritici - Min Jiao; Dan Yu; Chenglong Tan; Jia Guo; Dingyun Lan; Ershang Han; Tuo Qi; Ralf Thomas Voegele; Zhensheng Kang; Jun Guo (Environmental Microbiology, 2017)
Summary Calcium/calmodulin‐dependent kinases (CaMKs) are Ser/Thr protein kinases (PKs) that respond to changes in cytosolic free Ca 2+ and play diverse roles in eukaryotes. In fungi, CAMKs are generally classified into four families CAMK1, CAMKL, RAD53 and CAMK‐Unique. Among these, CAMKL constitutes the largest family. In some fungal plant pathogens, members of the CaMKL family have been shown to be responsible for pathogenesis. However, little is known about their role(s) in rust fungi. In this study, we functionally characterized a novel PK gene, PsCaMKL1 , from Puccinia striiformis f. sp. tritici ( Pst ). Ps CaMKL1 belongs to a group of PKs that is evolutionarily specific to basidiomyceteous fungi. Ps CaMKL1 shows little intra‐species polymorphism between Pst isolates. PsCaMKL1 transcripts are highly elevated at early infection stages, whereas gene expression is downregulated in barely germinated urediospores under KN93 treatment. Overexpression of PsCaMKL1 in fission yeast increased resistance to environmental stresses. Knock down of PsCaMKL1 using host‐induced gene silencing (HIGS) reduced the virulence of Pst accompanied by reactive oxygen species (ROS) accumulation and a hypersensitive response. These results suggest that Ps CaMKL1 is a novel pathogenicity factor that exerts it virulence function by regulating ROS production in wheat.

Anti-inflammatory Mechanism of Bone Marrow Mesenchymal Stem Cell Transplantation in Rat Model of Spinal Cord Injury - Dongji Han; Chenglong Wu; Qiuju Xiong; Ling Zhou; Yuke Tian (Cell Biochemistry and Biophysics, 2015)

Effects of dietary astaxanthins on pigmentation of flesh and tissue antioxidation of rainbow trout (Oncorhynchus mykiss) - Juanjuan Zhang; Xiaoqin Li; Xiangjun Leng; Chenglong Zhang; Zhiying Han; Feige Zhang (Aquaculture International, 2013)